Epistemological Backgrounds Of The Linguistic Term Through The Efforts Of Mustafa Ghalfan - ketfi, nour; rahmani, zahreddine (El Omda in Linguistics and Discourse Analysis, 2024)
Terms are an explicit and genuine representation of concepts and the expressive tool of knowledge and science, and thus I opted to describe the keys of science. They carry conceptual semantic loads based on special epistemological backgrounds. From this point of view, the article aims to reveal these epistemological backgrounds of the linguistic term in Arabs, in ancient and modern times, through the efforts of Ghalfan. Therefore, we will address the definition of the epistemological foundations on which the linguistic term was based by explaining it, knowing its background, analyzing its dimensions, and tracing its effects. We have endeavored to limit the study to the most important terms that Ghalfan has presented in structural linguistics. To achieve this, the study adopted the descriptive approach, as well as the inductive approach, to show at the end of the study the impact of epistemology on the multiplicity of linguistic terminology